2021
DOI: 10.3390/ijerph18105121
|View full text |Cite
|
Sign up to set email alerts
|

Longitudinal Effects of Motivation and Physical Activity on Depressive Symptoms among College Students

Abstract: High prevalence of depression and physical inactivity have been consistently reported among college students, especially in females. Guided by Lubans et al.’s conceptual framework, the primary purpose of this study was to examine the longitudinal relationships of PA motivation with leisure-time PA and depressive symptoms among college students over one academic year. Employing a longitudinal repeated measure design, 1004 college students in China were recruited in this study (28.3% males and 71.7% females; M a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0
5

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 34 publications
0
6
0
5
Order By: Relevance
“…The trends of increasing major depressive symptoms across all ages (i.e., children to elders) have centered the prevention efforts for depression [1][2][3][4][5][6][7]. Of particular note is the steep rise in major depressive episodes among adolescents (14-20% between 15-and 18-year-olds; [8][9][10]).…”
Section: Introductionmentioning
confidence: 99%
“…The trends of increasing major depressive symptoms across all ages (i.e., children to elders) have centered the prevention efforts for depression [1][2][3][4][5][6][7]. Of particular note is the steep rise in major depressive episodes among adolescents (14-20% between 15-and 18-year-olds; [8][9][10]).…”
Section: Introductionmentioning
confidence: 99%
“…In fact, physical activity is essential to health among the youth. Only about one-third of Chinese college students achieved the National Fitness Program’s recommendation for moderate physical activity [ 31 ]. Students who more physically active had better self-perceived health [ 32 ], and they did not think they had any health problems [ 33 ].…”
Section: Discussionmentioning
confidence: 99%
“…The investigation made by the authors of [ 73 ] at the level of young people in Australia (10–16 years old) demonstrated that school physical activities and leisure activities, participation in representative teams of educational institutions were associated with reduced levels of stress and depression, combined with reduced time spent in front of screens (leisure time screen). The importance of physical activity in reducing depression for students in China in the first year of study is mentioned by the authors of [ 74 ], the physically active have high motivation to participate in leisure physical activities and reduced depressive symptoms compared to sedentary people.…”
Section: Discussionmentioning
confidence: 99%